Entitas Superlunar dan Sublunar dalam Metafisika Ikhwān Al-Ṣafā - Dedy Ibmar (ILMU USHULUDDIN, 2017)
This paper seeks to examine the metaphysical views of Ikhwān al-Ṣafā. The metaphysical view that developed in the 10th century AD is a unique view that places nature more fully as a spiritual and material entity simultaneously. After several centuries, modern science, especially through modern cosmology has abandoned the spiritual-metaphysical aspects of the universe, and only recognizes nature as a material-physical entity. It was for centuries that metaphysics was rejected as the epistemological basis of science. Yet in the view of Ikhwān al-Ṣafā sublunar material things are nothing but entities born from metaphysical entities. The metaphysics of Ikhwān al-Ṣafā, will show the boundary between macro-spiritual things called superlunar and physical micro-entities called sublunar.